2016
DOI: 10.1021/acs.biochem.5b01115
|View full text |Cite
|
Sign up to set email alerts
|

Conserved SecA Signal Peptide-Binding Site Revealed by Engineered Protein Chimeras and Förster Resonance Energy Transfer

Abstract: Signal peptides are critical for the initiation of protein transport in bacteria by virtue of their recognition by the SecA ATPase motor protein followed by their transfer to the lateral gate region of the SecYEG protein-conducting channel complex. In this study, we have constructed and validated the use of signal peptide-attached SecA chimeras for conducting structural and functional studies on the initial step of SecA signal peptide interaction. We utilized this system to map the location and orientation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 45 publications
(129 reference statements)
0
17
0
Order By: Relevance
“…The determined distances have a larger error than that obtained experimentally for the efficiencies alone to account for the error introduced by the uncertainty in dye position as determined from steady-state anisotropy values (21,30,31). Using this information, we could position the signal peptide and early mature region of PhoA within the SecA-SecYEG complex.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The determined distances have a larger error than that obtained experimentally for the efficiencies alone to account for the error introduced by the uncertainty in dye position as determined from steady-state anisotropy values (21,30,31). Using this information, we could position the signal peptide and early mature region of PhoA within the SecA-SecYEG complex.…”
Section: Resultsmentioning
confidence: 91%
“…1). We also demonstrated that the lambda receptor signal peptide, KRRLamB, bound to SecA in the same location and orientation as its PhoA counterpart, indicative of a common binding site and orientation (21).…”
mentioning
confidence: 69%
See 3 more Smart Citations